Aspects of Evil in William Golding’s Novel “LORD OF THE FLIES” - Shehriyar Younas; Osama Hassan; Simab Gul (Journal for Social Science Archives, 2025)
William Golding's Lord of the Flies is a novel that tells the story of kids on an unknown island. They reach this island due to the accident of a ship when they are going to school. Golding portrays the evil nature of humans in an obvious way. Students show good manners at first, but soon they become wild when they realize that there is no elder on the lagoon for supervision. The protagonist in the novel crosses every limit of modesty. He takes a naked bath in the water. Firstly, they follow the rules, but gradually everyone starts breaking the rules made by them. Golding tries to convey that human nature has evil which is inside every individual. There are two types of evils in the world. One is moral, and the second is natural evil. Natural evil is not responsible for the bad things in the world. It is a moral evil that will cause natural evil. In case of devastation, it is our moral evil that causes wrath. Everyone is brutal, but he is trapped by social norms, values, and codes. The antagonist of the play is the most brutal person. He kills children and hints more the required.